EFFECTS OF SUBSTITUTION OF BASAL FEED WITH FERMENTED NON CONVENTIONAL FEED IN RATION ON PHYSICAL QUALITY OF BROILER MEAT - Pangestika, Sandra Dwi; dihansih, elis; Anggraeni, Anggraeni (Universitas Djuanda Bogor, 2018)
Demand for broiler meat for fulfilling people’s need for animal protein is increasing as it is nutritious and cheap in price. This study was aimed at assessing the effects of substitution of basal feed with fermented non conventional feed in ration on physical quality of broiler meat. The study was conducted from May to June 2017 at the Animal Laboratory of Djuanda University, Bogor. Proximate analysis on palm kernel cake, coconut cake, tofu waste product, and dried cassava was conducted at the laboratory of the Research Center of Biological Resources and Biotechnology, Bogor Agricultural University. Twenty-four of broiler chickens were used. A completely randomized design with 6 treatments and 4 replicates was used. Treatments consisted of 100% basal ration (R0, control), 90% basal ration + 10% non conventional feed (R1), 75% basal ration + 25% non conventional feed (R2), 60% basal ration + 40% non conventional feed (R3), 45% basal ration + 55% non conventional feed (R4), and 30% basal ration + 70% non conventional feed (R5). Results showed that water holding capacity, water content, and tenderness of meat were significantly different (P<0.05) but pH and cooking loss were not (P>0.05). Key words: broiler chicken, non conventional feed, meat physical quality